Are preschool children active enough in Shanghai: an accelerometer-based cross-sectional study. Issue 4 (25th April 2019) - Quan, Minghui; Zhang, Hanbin; Zhang, Jiayi; Zhou, Tang; Zhang, Jinming; Zhao, Guanggao; Fang, Hui; Sun, Shunli; Wang, Ru; Chen, Peijie
Abstract : Objective: Engaging in physical activity (PA) plays an important role in promoting physical and mental health, but the PA data for Chinese preschool children are lacking. This study aims to objectively assess the PA levels of preschool children in Shanghai, China and to evaluate their PA levels relative to age-specific recommendations. Design, setting and participants: A cross-sectional study was conducted among preschool children in Shanghai, city of China. There were a total of 303 preschool children (boys, 174; girls, 129) recruited from eight kindergarten classes in the Yangpu and Baoshan Districts of Shanghai. Main outcome measures: Daily PA was assessed using ActiGraph GT3X + accelerometers for seven consecutive days. Children were required to have data from at least 2 weekdays and 1 weekend day, with a minimum daily wear time of 480 min to be included in the analysis. Results: Preschool children in Shanghai accumulated, on average, 70.9 min of moderate-to-vigorous PA (MVPA) and 168.0 min of total PA (TPA) per day (d). Boys engaged in more MVPA and TPA than girls (72.8 min/day vs 68.3 min/day and 171.9 min/day vs 162.9 min/day, respectively). Overall, 72.9% of the participants met the age-specific recommendations of MVPA, while 35.3% met TPA recommendations. Conclusions: Findings of this study warn of the insufficiency of PA in Shanghai preschool children, suggesting there is substantial room to improve their PA. Trial registration number: ChiCTR-OOC-15007439; Results.